Eﬀect of growing systems on yield and quality of lettuce (Lactuca sativa) under subtropical climatic condition - Anand Sahil; SR Singh; AK Singh; Kumar, Sonu (Current Horticulture, 2025)
The study was carried out to indentify suitable growing system for higher yield of lettuce (Lactuca sativa L.) at ICAR-CISH, Lucknow during 2021-22. The experiment was conducted with two growing, aeroponic and geoponic systems. Five lettuce varieties were sown in portray by using mixture combination of coco peat, vermiculite, and perlite in a 3:1:1 ratio. After 30 days, plants were transplanted in both aeroponic and geoponic systems. The maximum yield (181.90 q/ha) was found in aeroponic system followed by geoponic system (144.73 q/ha). However, vitamin C content and total carotenoid content were non signiﬁcantly highest (12.09mg/100g) and (6.13) in geoponic system respectively. Chlorophyll ‘a’ (0.70 mg/g FW) was observed in geoponic system, while chlorophyll ‘b’ (0.119 mg/g FW) under aeroponic system.